dataset for 'A Cyclic Self-enhancement Technique for Complex Defect Profile Reconstruction based on Thermographic Evaluation' - Liu, Haochen; Wang, Shuozhi; Deng, Kailun; Zhao, Yifan (Cranfield University, 2023)
The dataset for this research is the synthetic dataset combined FEM simulation and experimental results of a Pulsed Thermography (PT) inspection for flat-bottom hole defects in metal materials.
Keywords: 'Non-destructive Testing and Evaluation'; 'Complex defect reconstruction'; 'Generative Adversarial Network'; 'Thermographic data augmentation'; 'Self-enhancement'